A Pemberdayaan Santri di Rumah Amal MIS Hubbullah Pekanbaru Melalui Produksi Nugget Ikan Patin - Silvia Reni Yenti; Amun Amri; Ahmad Fadli; Zultiniar Zultiniar; Sunarno Sunarno; Wisrayetti Wisrayetti (Journal of Community Engagement Research for Sustainability, 2021)
Counseling activities and training on making catfish nuggets have been carried out for the students at the MIS Hubbullah Charity House Pekanbaru. The activity was carried out by lecturers at the Department of Chemical Engineering, FT UNRI who were assisted by students. Evaluation of activities is carried out both before and after activities are carried out. From the results of the activity evaluation, it was found that there was an increase in the understanding and ability of participants in processing catfish into fish nuggets by 94.4%. Based on a follow-up survey conducted by the service team, it was found that the students of MIS Hubbullah continued the activities of making these catfish nuggets and even made a label for the product packaging of catfish nuggets as one of their business units.